PEMANFAATAN HASIL HUTAN BUKAN KAYU SEBAGAI BAHAN INSEKTISIDA ALAMI - Cahyana, Budi Tri; Arhamsyah, Arhamsyah (Kementerian Perindustrian, 2012)
Non-timber forest products (NTFPs) such as the root of Akar Wangi (Vetiveria zizainoides), Durian’s bark (Durio zibethinus Murr), Jaringau (Acorus Calamus L.), Liligundi (Vitex trifolia), Gemor bark (Alseodaphne spp.), and Neem seeds (Azadirachta indica A. Juss.) have good potential as a natural insecticide. They can be used for anti-mosquito materials that can be prevent the development of vector-borne Dengue Haemorrhagic Fever (DHF). Disruptive effects of the plants to the insects come from the odor which produces from the plant. Judging from the compounds that contained in non-timber forest products (NTFPs), beside used as anti-mosquito repellent, it can also used as other pests repellant such as bugs, termites, ants, etc. The end product also can be diversed as insect repellent burns, topical / lotion, spray, and others.Keywords : akar wangi, durian bark, jariangau, liligundi, gemor bark, mimba, natural insecticide